TAX POLICY AND FISCAL CONSOLIDATION ON CORPORATE INCOME TAX - Juhandi, Nendi; Fahlevi, Mochammad; Setiadi (Journal of Business, Management, and Accounting, 2019)
Tax is the largest state revenue, even from year to year, the number of state revenues from taxation in the State Budget always increases. Tax is one of the important sources of revenue to finance expenditures, both in the form of routine expenditure and development expenditure. The government also makes tax a monetary policy tool. However, for companies or business actors, tax is a burden that will affect net income. Therefore, this study was conducted to determine how much influence the application of Article 21 Income Tax, fiscal correction and deferred tax on corporate income tax on automotive and component sub-sector issuers on the Indonesia Stock Exchange. The research objective was to determine the application of Article 21 Income Tax, fiscal correction and deferred tax on automotive and component sub-sector issuers on the Indonesia Stock Exchange, and the extent of the effect of applying Article 21 Income Tax, fiscal correction and deferred tax on corporate income tax on automotive sub-sector issuers and components on the Indonesia Stock Exchange. This research was carried out using data obtained from the Indonesia Stock Exchange. The method of collecting data uses secondary data 12 companies listed in the automotive and component sub-sector on the Indonesia Stock Exchange from 2009 to 2013. The data obtained is then processed with the help of SPSS software version 20.00. Overall the results of the study indicate that the application of Article 21 Income Tax, fiscal correction, and deferred tax simultaneously have a significant effect on corporate income tax, while the partial test of the application of Article 21 Income Tax and deferred tax has a significant effect on corporate income tax, while tax correction is partially influential not significant to corporate income tax